ChemInform Abstract: Graphene‐Supported Substoichiometric Sodium Tantalate as a Methanol‐Tolerant, Non‐Noble‐Metal Catalyst for the Electroreduction of Oxygen. Issue 26 (June 2015) - Sebastian, David; Baglio, Vincenzo; Sun, Shuhui; Tavares, Ana C.; Arico, Antonino S.
Abstract The graphene‐supported Na2Ta8O21‐x electrocatalyst (50 wt% Ta2O5, 50 wt% graphene) is obtained by sonicating graphene in an aqueous TaCl5 solution at pH 10.9 (adjusted with NaOH) followed by drying and heating under Ar (900 °C, 90 min).